2020
DOI: 10.1371/journal.pone.0236257
|View full text |Cite
|
Sign up to set email alerts
|

Cancer screening activity results in overdiagnosis and overtreatment of papillary thyroid cancer: A 10-year experience at a single institution

Abstract: Background It is estimated that one of the potential cause of the increasing prevalence of thyroid cancer (TC) is the easier and widespread access to diagnostic tools. If an individual evaluates the thyroid gland due to a mentioned mechanism without considering TC risk factors or symptoms, we can describe this phenomenon as cancer screening activity (CSA).

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
18
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 14 publications
(18 citation statements)
references
References 40 publications
0
18
0
Order By: Relevance
“…Paradoxically, to make this issue more interesting, or even complex, some other authors recommend that people with excess body weight be encouraged to join cancer screening programs [ 9 ]. We presented our opinion concerning “cancer screening activity” in a previous study; however, we did not analyze PTC screening according to BMI [ 19 ].…”
Section: Introductionmentioning
confidence: 99%
“…Paradoxically, to make this issue more interesting, or even complex, some other authors recommend that people with excess body weight be encouraged to join cancer screening programs [ 9 ]. We presented our opinion concerning “cancer screening activity” in a previous study; however, we did not analyze PTC screening according to BMI [ 19 ].…”
Section: Introductionmentioning
confidence: 99%
“…In our earlier study, we described this phenomenon as “cancer screening activity”. 1 Cibas et al 2 estimated that TNs might be observed in 50% of patients aged 50 years, with a low overall malignancy risk of 5 to 7%.…”
Section: Introductionmentioning
confidence: 99%
“…The most commonly employed preoperative diagnostic tool for TN evaluation remains the ultrasound-guided fine needle aspiration biopsy (UG-FNAB) procedure. 1 , 2 On the basis of this screening test, The Bethesda System for Reporting Thyroid Cytopathology (TBSRTC) was introduced in 2009 2 and subsequently modified in 2017. 3 , 4 It consists of six categories that enhance and standardize TN management.…”
Section: Introductionmentioning
confidence: 99%
“…Despite the progressive increase in incidence, the disease-specific mortality in the US has increased marginally from 0.40 to 0.46 per 100,000 and can be accounted for by the advanced and dedifferentiated cancers that occur most commonly in an ageing population [9]. In 2020, 43,646 patients died from thyroid cancer (27,740 women and 15,906 men) (Global Cancer Observatory, IARC), almost no change from the 40,000 estimated global deaths in 2012 [6]. These trends of incidence and mortality are seen across the developed world, with pockets of extreme increase in incidence in countries where thyroid screening has been adopted, such as in South Korea [5,10,11].…”
Section: Epidemiology Of Dtcmentioning
confidence: 99%
“…In some European countries and the US, 45 to 70% of thyroid malignancies are considered "over diagnosed", based on studies comparing the expected and observed prevalence of thyroid cancer [26]. This conclusion is also inferred by the rise of early-stage thyroid cancer and the incongruity of there being more cancer with no change in mortality over decades [27]. The alternative explanation, that early diagnosis coupled with excellent treatment has compensated for a real thyroid cancer epidemic, appears less substantiated.…”
Section: Overdiagnosis and Overtreatmentmentioning
confidence: 99%